Prototypes and R&D for undulator-based positron sources - Moortgat-Pick Gudrid; Formela Manuel; Hamann Niclas; Lengler Tim; Lott Dieter; Loisch Gregor; Riemann Sabine; Sievers Peter; Tenholt Carmen; Yakopov Grigory (EPJ Web of Conferences)
The undulator-based positron source is baseline design for the ILC. Recent progress in particular on the undulator mask designs, optic matching devices (R&D for prototypes for pulsed solenoid, plasma lens) and on the target design (rotating wheel, material tests) are discussed. The adaption of an undulator-based positron source for the HALHF design as an upgrade option for the ILC is included as well.